A Geopolitical Study of the Indo-Pacific through the Theories of Ancient East and Modern West - Praveen Kumar (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
The core of the debates on politics through times and regions is concerned with territories and exercise of power over the territories directed towards certain end(s). This is seen in the theories of Ancient India, of which Kautalyas Arthashastra is but a representative literature. Much later in time, geopolitical theories in the west during the twentieth-century significantly highlighted this point. This study aims to understand geopolitics in the Indo-Pacific if Kautalya's ideas and geopolitical choice theories from the west are applied, then results of the study would be the same as has been affirmed in the opening sentences. Methodologically, the study, qualitative in approach though, looks at the data available in the secondary source materials to test if territories determine the power dynamics at a given point of time. Kautalyas Arthashashtra offers a good theoretical insight that can explain the contemporary geopolitical structures and behavior of the states. The theory has scientific and empirical elements that can help explain issues of aggression, conflict and peace. Peace (Shamah) and conflict or war (Vigraha) are shaped by the inter-dependent factors, both, tangible and intangible, as well as, internal and external. While the study primarily explores œthe empirical and œthe scientific in Kautalyas Arthashashtra, but takes the twentieth-century western geopolitical theories to develop parameters of testability of the theory